Incorporating wind generation into LV microgrid system part II - Lin, Liu Yi. (2010)
The depletion of natural fossil fuels together with global warming is a pressing concern of the modern century and new energy alternatives needs to be considered. One such successful example will be wind generation. However, wind, being a variable source of energy, needs to be conditioned before it can be used as a reliable source. The main purpose of this report is to design the wind system control mechanism and simulate it using a DC drive to act as a wind turbine and control the generated output voltage magnitude and frequency to match those from the grid. As this has not been attempted by any previous student in the Laboratory of Clean Energy Research (LaCER), there is a need to build the required three phase Pulse-Width Modulated (PWM) back-to-back voltage fed converters hardware from scratch. After building the required hardware, designing and testing of the control mechanism is carried out. As wind generation is a variable speed operation, vector control needs to be implemented to ensure the dynamic performance is met. Using vector control and based on the dynamic model of the Doubly Fed Induction Generator (DFIG) rather than the steady state model, control approaches of each of the two back-to-back converters are obtained. Using these approaches, they are implemented in Matlab Simulink, then dSPACE and software ControlDesk are used to simulate the designed control mechanism in real time. Further investigations are still required for the back-to-back converters to work harmoniously together; however, much progress is obtained from them when they are controlled separately.